Effect of Watermelon and Carrot Combination Juice on Blood Pressure Changes in Hypertension Patients at Andalas Public Health Center Padang City - Salma, Salma; Kasmiyetti, Kasmiyetti; Yani, Irma Eva (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
Hypertension is one of the most prevalent non-communicable diseases and remains a major public health problem that increases the risk of cardiovascular morbidity and mortality. Dietary modification, especially increased intake of fruits and vegetables, is considered an effective non-pharmacological approach to control blood pressure. This study aims to examine the effect of giving a combination of watermelon and carrot juice on changes in blood pressure in hypertensive patients, using a pre-experimental design (one-group pretest-posttest design) with a purposive sampling technique involving 17 respondents. Data were analyzed using a dependent T-test. The results showed a significant decrease in both systolic and diastolic blood pressure after consuming the juice (p < 0.001). The average systolic pressure decreased from 149.00 mmHg to 133.00 mmHg, and the average diastolic pressure decreased from 93.65 mmHg to 87.47 mmHg. This study suggests that watermelon–carrot juice may serve as an affordable complementary option to support blood pressure control in hypertensive patients.